2009
DOI: 10.1359/jbmr.081252
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulation of Bone Traits Is Influenced by Sex and Reciprocal Cross in F2 Progeny From GK and F344 Rats

Abstract: A genome-wide linkage analysis to identify quantitative trait loci (QTLs) for bone phenotypes was performed in an F 2 intercross of inbred spontaneously type 2 diabetic GK and normoglycemic F344 rats (108 males and 98 females). The aim of the study was to locate genome regions with candidate genes affecting trabecular and cortical bone and to investigate the effects of sex and reciprocal cross. pQCT was used to determine tibial bone phenotypes in the F 2 rats, comprising reciprocal crosses with divergent mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 47 publications
(87 reference statements)
6
15
0
Order By: Relevance
“…Given the importance of mitochondria in energy and metabolism processes, it was not surprising that such interactions were observed. Similarly, differential reciprocal cross effects have been documented in other QTL mapping studies (Smith Richards et al, 2002;Lagerholm et al, 2009). Another explanation of this reciprocal cross effect could be a result of some effects from the Y chromosome.…”
Section: Epistatic Qtl Interactions With Myostatin Genesupporting
confidence: 65%
“…Given the importance of mitochondria in energy and metabolism processes, it was not surprising that such interactions were observed. Similarly, differential reciprocal cross effects have been documented in other QTL mapping studies (Smith Richards et al, 2002;Lagerholm et al, 2009). Another explanation of this reciprocal cross effect could be a result of some effects from the Y chromosome.…”
Section: Epistatic Qtl Interactions With Myostatin Genesupporting
confidence: 65%
“…Additionally, we previously reported that QTLs for trabecular and cortical tibial bone phenotypes measured by pQCT in (GK×F344) F2 crosses with divergent mtDNA are influenced by gender and reciprocal cross [24]. The more than 100 variant positions between GK and F344 mtDNA, including twelve non-synonymous amino acid changes in proteins required for ATP synthesis [25], support the involvement of mtDNA variants as a major factor behind the reciprocal cross effect.…”
Section: Introductionmentioning
confidence: 85%
“…A total of 192 genomewide microsatellite markers were genotyped and a genetic linkage map was generated as described previously [24]. Genetic linkage analysis was performed for each sex separately.…”
Section: Genotyping and Linkage Analysis Of Quantitative Traitsmentioning
confidence: 99%
See 2 more Smart Citations